Components of metabolic syndrome are independent predictors of mortality in patients with chronic liver disease: a population-based study. Issue 10 (26th July 2010) - Stepanova, Maria; Rafiq, Nila; Younossi, Zobair M
Abstract : Objective: Chronic liver disease (CLD) is a major cause of mortality and morbidity worldwide. The aim of this study was to assess the overall and liver-related mortality and their predictors in patients with CLD using population data. Methods: The Third National Health and Nutrition Examination Survey (NHANES III) and linked mortality data were utilised. Participants from NHANES III (1988–1994) and their mortality status were updated by the Center for Disease Control (CDC) as of 31 December 2006. In this study, the aetiology of CLD was based on available serological tests and clinical data. Each diagnostic cohort was compared with a cohort without liver disease using stratum-specific χ 2 . The Cox proportional hazard model was used for analysis, and HRs adjusted for all major confounders; overall mortality and cause-specific mortality were calculated for each type of liver disease. All analyses were run using SAS-callable SUDAAN 10.0 functions using remote access to the CDC Research Data Center server with restricted use linked mortality data. Results: The study cohort included 15 866 NHANES III participants with complete clinical, demographic, laboratory and mortality follow-up data. Of these, 235 subjects had alcohol-related liver disease (ALD), 66 had chronic hepatitis B (CH-B), 264 had chronic hepatitis C (CH-C), 991 were presumed to have non-alcoholic fatty liver disease (NAFLD) and 505 had other liver disease. Additionally, 13 004 subjects without evidence of liver disease served as controls. The analysis shows that type II diabetes (DM) and/or insulin resistance (IR) are independent predictors of overall mortality in CH-B, NAFLD and ALD (p <0.05). Additionally, DM, IR, obesity and metabolic syndrome could be independent predictors of liver-related mortality in CH-C, NAFLD and ALD. Conclusions: Components of metabolic syndrome are associated with overall and liver-related mortality in subjects with CLD.